Correlates of Suicidal Ideation in Adolescents: A Cross Sectional Study - Yasien, Saba; Siddiqui, Zaeema; Washdev, Washdev; Kumar, Ameet (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the factors associated with suicidal ideation among college students in Pakistan. Methodology: This was a cross sectional study, sample was selected randomly from public and private colleges located in different areas of Karachi, Pakistan. Data was collected from Sep 2014 to Feb 2015. 545 adolescents, aged 16 years to 19 years were selected by random sampling. Positive and negative suicide ideation Inventory, Personal Information Form, Beck hopelessness Scale, and Aga Khan Anxiety and Depression Scale were administered. Adolescents with any physical disability, chronic physical illness and any diagnosed psychiatric disease were excluded. Statistical analysis was done by using SPSS 14. Results: Descriptive statistics and Binary Logistic Regression analysis were used to analyse the collected data. The analysis revealed that gender, living in nuclear family setup, suicide attempt in past, a suicide attempt by family members, suicide attempt by friends, illness in family members, and the severity of hopelessness and symptoms of anxiety were found significantly correlated with the suicidal Ideation. Conclusion: Findings of the study evidenced that certain socio-demographic and psychological associated risk factors should be consider to design and implement strategies for intervention and prevention of suicidal behaviours. Limitations and implications of the present study have also been recommended. Keywords: Suicidal ideation, Adolescent, Students, Anxiety-Depression, Hopelessness